Frequency of Caesarean Delivery on maternal request in a private teaching hospital - Fozia Umber Qurashi , Saima Jabeen , Wajiha Alvi (Journal of Rawalpindi Medical College, 2020)
Introduction: Caesarean section rates are increasing worldwide. There are many reasons for this increasing caesarean section rate one of them is increasing requests by women for caesarean section in the absence of medical indications. Most women think that elective caesarean section is safe both for women and babies. Some clinician also considered caesarean section safe. An increasing rate of caesarean section is alarming in developed as well as underdeveloped countries. Objective: To investigate the frequency of caesarean section on maternal request and factors leading to it in a private teaching hospital. Materials and Methods: This was a cross-sectional descriptive study carried out at Shalamar hospital from 1st May 2018 to 30th April 2019. Women of all ages who were pregnant and were going to have caesarean delivery during the study period at Shalamar hospital. Results: There were 3438 total births during the study period. There were 2380(69%) caesarean section and 1058(31%) were normal vaginal deliveries. Caesarean section rate was 69%. Caesarean sections performed on maternal request were 167(7%) out of 2380 caesarean. Out of these 167 Seventy-two, 43.1% of women were those who already have a previous caesarean section for different non-recurrent indications and now they don’t want the trial of labour and requested for caesarean section. Forty, 24% of women requested for a caesarean section because of fear of labour pains and eighteen, 10.8% were those who had a bad experience of the previous child-birth. Twelve, 7.2% of women had fear of failed vaginal delivery and eight women had fear of trauma to baby and three, 1.8% had fear of perineal trauma during the trial of normal vaginal delivery. Six, 3.6% of women had some social reasons for caesarean section and six, 3.6% had some bad experience of normal delivery of their relatives or friends and two, 1.2% were those who were requesting caesarean section because of their family members preferences. Conclusion: Most of the women requesting for caesarean section were those who had previously trial of labour. We can control the caesarean section rate by proper counselling of pregnant women.